Functions of Agriculture and Rural Areas in View of Energy Management and Ecoservices Development in Poland - Wojciech ŻARSKI; Waldemar BOJAR (Communications of International Proceedings, 2022)
In the paper, a review of problems of sustainable development in the context of energy resources management and environmental challenges was undertaken with consideration of functions of agriculture and rural areas. The goal of this paper was to show the evolution of agriculture and rural areas through more effective energy and natural resources management in view of the current progressive tendencies important for the performance of the primary and secondary functions of agriculture and rural areas. Based on a critical study of literature, solutions to economic and social problems were shown through the impact of technological progress on farming with consideration of climate change and ecosystem damage using evolution in crop and animal cultivation, their protection, genetic selection and irrigation.
Keywords: Ecosystem Services; Sustainable Development; Management; Natural Resources; Energy